Inflammatory Myofibroblastic Tumor in Adult: A Rare Case - Nakarmi, Rajiv; Chen, Ming-Jenn; Ong, Khaa- Hoo; Shrestha, Muza; Maharjan, Sundar (Nepal Medical College Journal, 2021)
Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm of intermediate biologic potential. Inflammatory myofibroblastic tumor (IMT) of the alimentary tract often occurs in children or young adults, but may occur at any age. The lung is the most commonly affected location. However, it may appear in small bowel mesentery especially the distal ileum, mesotransverse colon, or greater omentum. A 35 years old female presented to out-patient department with complaint of mass in right abdomen since 1 month associated with loss of weight. Computed tomography of abdomen revealed a solid intraperitoneal mass arising from bowel mesentery. Laparoscopic excision of the tumor was performed and the histopathological examination of the mass revealed it to be an inflammatory myofibroblastic tumor arising from the omentum and large bowel mesentery. The post- operative period was uneventful with no evidence of tumor recurrence at follow up at 2 years. Inflammatory myofibroblastic tumor is a rare soft tissue tumor usually arising from lungs but tumor arising from the omental-mesenteric origin has also been documented. The precise diagnosis is made only by the histopathological evidence. Surgical resection is the treatment of choice.